Penerapan Teknologi Penyiraman Tanaman Sayuran Otomatis Berbasis Internet of Things - Noviandri, Dian; Amin, Harsya Rizqy (Journal of Computing and Informatics Research, 2025)
This research is based on the results of field observations, namely farmers who grow vegetables such as kale, pak choi and the like on dry land. Vegetables are watered in the morning and evening by farmers who are on duty every day until the harvest season arrives [1]. The purpose of the research is to create an automatic vegetable watering system based on Internet of Things, which can replace the farmer's task of watering vegetables [2]. The method used is Rapid Application Development (RAD) [3],by defining the tool needs, designing and making the tool. The result of this research is an IoT-based vegetable watering system and successfully replaces the farmer's task [4].